THANATOURISM PROFILE OF TURKEY - İlkay TAŞ (Fırat University, 2019)
Despite long dominance of general interest tourism on tourism mobility, there is an increasing interest for specialized tourism products. This brings about a challenge for tourism destinations which have based their product offer on sun and sea tourism. Aggravated with seasonality, dependence on sun and sea tourism increases the vulnerability of tourism destinations. Thanatourism is a special interest tourism which lives on death, fear, grief related feelings of people. Human relationship with death has been a controversial one. While the reality of death is acknowledged and sanctified, on one side it is avoided and on the other, it is approached. Thanatourism has arisen in this complicated terms. Thanatourism destinations can either be created on purpose or it is the result of historical experiences. Thanatourism can take various forms according to the dominant theme of the travel experience such as battlefield tourism, danger-zone tourism, Dracula tourism. Besides it is a form of cultural heritage tourism which connects generations and communities over difficult past memories. Considering the major share of sun and sea related products in Turkish tourism market and the risks associated with it, the study proposes thanatourism as an opportunity for